Enhancing Grade IV Student Learning Outcomes Through the Implementation of the Discovery Learning Model: A Classroom Action Research on the Theme of Caring for Living Things - Sri Hastati; Nur Afni; Abdul Wahid (South Sulawesi Education Development (SSED), 2024)
This research examines the application of the Discovery Learning learning model to improve student learning outcomes on the theme of caring for living things for class IV students at SD Inpres Panaikang 1, Makassar City. The main problem in this research is the low learning outcomes of class IV students at SD Inpres Panaikang 1 Makassar City. The aim of this research is to apply the discovery learning model to improve student learning outcomes. This research is a classroom action research (CAR) method using the Kemmis and Taggart model. The research subjects were fourth grade students at SD Inpres Panaikang 1, Makassar City. This research consists of 2 cycles, each cycle consisting of planning, implementation, observation and reflection stages. The data collection techniques used in this research were observation and test techniques. The results of the research showed that there was an increase in students' average scores and students' learning completion. The average value in cycle I was 66.67 and in cycle II it increased to 81.11. Student learning completeness in cycle I was 44.44% and in cycle II it increased to 88.89%.